Molecular Docking And Molecular Dynamics Of 3-O-Octanoylcatechin Interactions Against Aldose Reductase - Soib’, Shikin Faezah (2019)
This study was conducted to search for potential aldose reductase (AR) inhibitors among the chosen catechin derivatives using computational methods. Molecular docking, molecular dynamics (MD) simulation and molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) free energy calculation were performed to investigate the interactions of AR with the catechin derivatives. A total of 14 ligands of catechin derivatives were submitted for molecular docking. Molecular docking results revealed ligand 2 (3-o-octanoylcatechin) has the best interactions and lowest binding energy with AR. A 100 ns molecular dynamics (MD) simulation was conducted for both AR/NADP+/quercetin (standard) and AR/NADP+/ligand 2. The results of MD analysis confirmed the stability of the AR/NADP+/ligand 2 complex based on the results of root-mean-square deviation (RMSD), radius of gyration (Rg) and secondary structure analysis. The root-mean-square fluctuations (RMSF) results indicated that there are no major changes in the structure and conformation of the protein upon the binding of ligand 2. The hydrogen bond analysis showed that ligand 2 has a high number and occupancy of intermolecular hydrogen bond formation with Trp111 (43.2 %), Glu120 (24.3 %), His110 (24.2 %), Gln49 (8.5 %) and Val47 (2.0 %) throughout the simulation compared with quercetin. The MM-PBSA free energy calculation showed lower total binding energy of ligand 2 (-127.62 ± 10.82 kJ/mol) compared with quercetin (-50.10 ± 9.74 kJ/mol).